2013
DOI: 10.4049/jimmunol.1203261
|View full text |Cite
|
Sign up to set email alerts
|

In Kidney Transplant Patients, Alemtuzumab but Not Basiliximab/Low-Dose Rabbit Anti-Thymocyte Globulin Induces B Cell Depletion and Regeneration, Which Associates with a High Incidence of De Novo Donor-Specific Anti-HLA Antibody Development

Abstract: In this single-center matched-cohort study, we evaluated the phenotype of repopulating B cells and its correlation with donor-specific anti-HLA Ab development and long-term graft function in 16 renal transplant recipients and 32 age- and gender-matched controls induced with alemtuzumab or basiliximab (Bas)/low-dose rabbit anti-thymocyte globulin (rATG), respectively. Alemtuzumab, but not Bas/rATG, profoundly depleted peripheral B cells in the first 2 mo posttransplantation. Early posttransplant, naive B cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 52 publications
(51 reference statements)
5
60
2
1
Order By: Relevance
“…45 However, although this hypothesis is interesting, it has been challenged by recent conflicting reports from two independent groups showing that alemtuzumab-induced B cell depletion/reconstitution is associated with a higher incidence of AMR compared with induction with ATG. 46,47 Basiliximab is a chimeric mousehuman nondepleting mAb targeting the a-chain (CD25) of the IL-2 receptor (Figure 1). Basiliximab was developed for induction therapy on the basis of the concept that it would block IL-2 binding, thereby inhibiting T cell proliferation.…”
Section: Effect Of Induction Therapy On Dndsa Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…45 However, although this hypothesis is interesting, it has been challenged by recent conflicting reports from two independent groups showing that alemtuzumab-induced B cell depletion/reconstitution is associated with a higher incidence of AMR compared with induction with ATG. 46,47 Basiliximab is a chimeric mousehuman nondepleting mAb targeting the a-chain (CD25) of the IL-2 receptor (Figure 1). Basiliximab was developed for induction therapy on the basis of the concept that it would block IL-2 binding, thereby inhibiting T cell proliferation.…”
Section: Effect Of Induction Therapy On Dndsa Generationmentioning
confidence: 99%
“…Their mechanism of action is diverse and includes interference with intracellular transcription factors and signaling pathways of several surface receptors, including the T cell antigen receptor 52 and downstream kinases. 53 High doses of corticosteroids (.1 mg/kg), used for induction therapy in transplantation, also induce lymphocyte apoptosis (including B cells) 46,54 and can prevent in vitro differentiation of B cells into plasma cells. 55 High concentrations of corticosteroids are also likely to interfere with Fc g-receptor signaling, including the inhibitory Fc g-RIIb, which acts as a key negative modulator of B cell function and controls bone marrow plasma cell apoptosis.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…A recent study by Ayasoufi noted that administration of ATG a week prior to transplant was substantially superior in inhibiting anti-donor T cell responses than at the time of transplant, suggesting that ATG has the ability to target preexisting donor-reactive memory T cells (14). Importantly, ATG induces Tregs following immune reconstitution, indicating that rATG therapy may also suppress B cells and DSA generation via activation of Tregs (16)(17)(18). Further in vitro and clinical studies are needed to investigate these specific mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different investigators reported efficacy of alemtuzumab treatment in expansion of transitional B cells and regulatory B cells during kidney transplants. 35,36 The proper mechanism of such repopulation of Breg and Treg cells after depletion of alloreactive cells is not clear and subject to in- Single-center retrospective study involving Higher incidence of antibody-mediated rejection (AMR), and kidney transplant patients between similar incidence of acute cellular rejection, 1-year graft survival, Transplant Proc. Table 2.…”
Section: Alemtuzumab As Immunomodifier In Transplant Therapymentioning
confidence: 99%